SPOP-mediated ubiquitination and degradation of PDK1 suppresses AKT kinase activity and oncogenic functions - Qiwei Jiang; Nana Zheng; Lang Bu; Xiaomei Zhang; Xiaoling Zhang; Yuanzhong Wu; Yaqing Su; Lei Wang; Xiaomin Zhang; Shancheng Ren; Xiangpeng Dai; Depei Wu; et al. (Molecular Cancer)
Abstract Background 3-phosphoinositide-dependent protein kinase-1 (PDK1) acts as a master kinase of protein kinase A, G, and C family (AGC) kinase to predominantly govern cell survival, proliferation, and metabolic homeostasis. Although the regulations to PDK1 downstream substrates such as protein kinase B (AKT) and ribosomal protein S6 kinase beta (S6K) have been well established, the upstream regulators of PDK1, especially its degrader, has not been defined yet. Method A clustered regularly interspaced short palindromic repeats (CRISPR)-based E3 ligase screening approach was employed to identify the E3 ubiquitin ligase for degrading PDK1. Western blotting, immunoprecipitation assays and immunofluorescence (IF) staining were performed to detect the interaction or location of PDK1 with speckle-type POZ protein (SPOP). Immunohistochemistry (IHC) staining was used to study the expression of PDK1 and SPOP in prostate cancer tissues. In vivo and in vitro ubiquitination assays were performed to measure the ubiquitination conjugation of PDK1 by SPOP. In vitro kinase assays and mass spectrometry approach were carried out to identify casein kinase 1 (CK1) and glycogen synthase kinase 3 (GSK3)-mediated PDK1 phosphorylation. The biological effects of PDK1 mutations and correlation with SPOP mutations were performed with colony formation, soft agar assays and in vivo xenograft mouse models. Results We identified that PDK1 underwent SPOP-mediated ubiquitination and subsequent proteasome-dependent degradation. Specifically, SPOP directly bound PDK1 by the consensus degron in a CK1/GSK3β-mediated phosphorylation dependent manner. Pathologically, prostate cancer patients associated mutations of SPOP impaired PDK1 degradation and thus activated the AKT kinase, resulting in tumor malignancies. Meanwhile, mutations that occurred around or within the PDK1 degron, by either blocking SPOP to bind the degron or inhibiting CK1 or GSK3β-mediated PDK1 phosphorylation, could markedly evade SPOP-mediated PDK1 degradation, and played potently oncogenic roles via activating the AKT kinase. Conclusions Our results not only reveal a physiological regulation of PDK1 by E3 ligase SPOP, but also highlight the oncogenic roles of loss-of-function mutations of SPOP or gain-of-function mutations of PDK1 in tumorigenesis through activating the AKT kinase.